PENGARUH LOKASI TERHADAP REVISIT DENGAN MEDIASI KEPUASAN DAN MEDIATOR CITRA RASA DAN HARGA PADA PRODUK TEHBOTOL SOSRO - Ali Maskuri; Andika Aisyah Setiadji; Nadine Arofafi Atus Safina; Yuki Niken Agfira Kitatrah; Surya Bintarti (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
Based on existing data, Indonesia is in the 3rd highest position in the ASEAN region as a society with a level of consumption of packaged sweet drinks. Tehbotol Sosro owned by PT Sinar Sosro, which is a pioneer of packaged tea drinks, occupies second place in the Top Brand Awards distribution of ready-to-drink tea in packs from various other manufacturers affect the ranking and sales of Teh botol Sosro although it has been involved in packaged tea drinks for a long time. The purpose of this study was to examine the effect of location on revisiting by mediating satisfaction and taste and price image mediators. The research was conducted within the boundaries of the community area of the Bekasi district. The number ofsamples was obtained by 55 respondents. Data collection used a questionnaire and then analyzed with SmartPLS. The research shows that location which is moderated by taste image has no effect on satisfaction, a location that is moderated by price has no effect on satisfaction but the location moderator variable has a direct effect as a latent variable on satisfaction (mediator predictor) while location which is mediated by satisfaction affects revisit.